2015
DOI: 10.1007/s00508-015-0716-8
|View full text |Cite
|
Sign up to set email alerts
|

Talc pleurodesis improves survival of patients with malignant pleural effusions: case-control study

Abstract: The patients treated with talc pleurodesis had a significantly longer average survival than the patients without such a treatment, especially in the group with the breast cancer and in groups with better performance status. This may indicate that talc pleurodesis, apart from its symptomatic effect on the cessation of pleural effusion, may have a direct antitumour effect as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Whilst pleurodesis aims to palliate symptoms rather than extend survival, one retrospective non-randomised study found talc poudrage pleurodesis was associated with longer survival compared with repeated thoracentesis [40]. However, the authors conflated correlation with causality, and ignored potential confounding by indication in the two treatment arms.…”
Section: Other Issues Regarding Talc Pleurodesismentioning
confidence: 99%
“…Whilst pleurodesis aims to palliate symptoms rather than extend survival, one retrospective non-randomised study found talc poudrage pleurodesis was associated with longer survival compared with repeated thoracentesis [40]. However, the authors conflated correlation with causality, and ignored potential confounding by indication in the two treatment arms.…”
Section: Other Issues Regarding Talc Pleurodesismentioning
confidence: 99%
“…We read with interest the article entitled 'Role of early definitive management for newly diagnosed malignant pleural effusion related to lung cancer' by Chiang et al 1 We have been particularly interested in the management of pleural effusion in patients with lung cancer, [2][3][4] and we would like to raise four issues arising from the article by Chiang et al…”
Section: To the Editorsmentioning
confidence: 99%
“…Interestingly, pleurodesis may have an antitumor effect and alter the natural history of cancers by inducing inflammation and increasing the survival rates among the mesothelioma patients with MPE. 23,75…”
Section: Malignant Pleural Effusionsmentioning
confidence: 99%